The Impact of Storage Temperature on the Morphology, Viability, Cell Number and Metabolism of Cultured Human Conjunctival Epithelium. (January 2015) - Eidet, Jon R.; Utheim, Øygunn A.; Islam, Rakibul; Lyberg, Torstein; Messelt, Edvard B.; Dartt, Darlene A.; Utheim, Tor P.
Abstract Purpose: To evaluate the effect of storage temperature on the morphology, viability, cell number and metabolism of cultured human conjunctival epithelial cells (HCjEs). Materials and Methods: Three-day cultured HCjEs were stored at nine different temperatures between 4 °C and 37 °C for four and seven days. Phenotype was assessed by immunofluorescence microscopy, morphology by scanning electron microscopy, viability and cell number by a microplate fluorometer and glucose metabolism by a blood gas analyzer. Results: Cultured cells not subjected to storage expressed the conjunctival cytokeratins 7 and 19 and the proliferation marker proliferating cell nuclear antigen. Cell morphology was best maintained following four-day storage between 12 °C and 28 °C and following 12 °C storage after seven days. Assessed by propidium iodide uptake, the percentage of viable cells after four-day storage was maintained only between 12 °C and 28 °C, whereas it had decreased in all other groups (p < 0.05; n = 4). After seven days this percentage was maintained in the 12 °C group, but it had decreased in all other groups, compared to the control (p < 0.05; n = 4). The total number of cells remaining in the cultures after four-day storage, compared to the control, had declined in all groups (p < 0.05; n = 4), except 12 °C and 20 °C groups. Following seven days this number had decreased in all groups (p < 0.01; n = 4), except 12 °C storage. Four-day storage at 12 °C demonstrated superior preservation of the number of calcein-stained viable cells (p < 0.05) and the least accumulation of ethidium homodimer 1–stained dead cells (p < 0.001), compared to storage at 4 °C and 24 °C (n = 6). The total metabolism of glucose to lactate after four-day storage was higher in the 24 °C group compared to 4 °C and 12 °C groups, as well as the control (p < 0.001; n = 3). Conclusions: Storage at 12 °C appears optimal for preserving the morphology, viability and total cell number in stored HCjE cultures. The superior cell preservation at 12 °C may be related to temperature-associated effects on cell metabolism.